7 rules for positive, productive change : micro shifts, macro results - Derby, Esther (Berrett-Koehler Publishers, 2019)
Even if you don't have change management in your job description, your job involves change. Change is a given, as organizations evolve with market and technology advances and adapt to new challenges. These are not simple issues with one right answer. Responding in complex environments requires trial and error. learning and unlearning. The answer is not more rigorous planning but rather an agile approach that engages, empowers, and attracts people to create and own a new way. In 7 Rules for Positive, Productive Change, Esther Derby offers a set of heuristics-guides to problem solving- that will help you navigate complex change in your environment."--Book cover